Quality appraisal in systematic literature reviews of studies eliciting health state utility values: Conceptual Considerations - Muchadeyi, Muchandifunga Trust; Hernandez-Villafuerte, Karla; Di Tanna, Gian Luca; Eckford, Rachel; Feng, Yan; Meregaglia, Michela; Peasgood, Tessa; Petrou, Stavros; Ubels, Jasper; Schlander, Michael (PharmacoEconomics, 2024)
Background The increasing number of studies that generate health state utility values (HSUVs) and the impact of HSUVs on cost-utility analyses make a robust tailored quality appraisal (QA) tool for systematic reviews of these studies necessary. Objective This study aimed to address conceptual issues regarding QA in systematic reviews of studies eliciting HSUVs by establishing a consensus on the definitions, dimensions and scope of a QA tool specific to this context. Methods A modified Delphi method was used in this study. An international multidisciplinary panel of seven experts was purposively assembled. The experts engaged in two anonymous online survey rounds. After each round, the experts received structured and controlled feedback on the previous phase. Controlled feedback allowed the experts to re-evaluate and adjust their positions based on collective insights. Following these surveys, a virtual face-to-face meeting was held to resolve outstanding issues. Consensus was defined a priori at all stages of the modified Delphi process. Results The response rates to the first-round and second-round questionnaires and the virtual consensus meeting were 100%, 86% and 71%, respectively. The entire process culminated in a consensus on the definitions of scientific quality, QA, the three QA dimensions—reporting, relevance and methodological quality—and the scope of a QA tool specific to studies that elicit HSUVs. Conclusions Achieving this consensus marks a pivotal step towards developing a QA tool specific to systematic reviews of studies eliciting HSUVs. Future research will build on this foundation, identify QA items, signalling questions and response options, and develop a QA tool specific to studies eliciting HSUVs.